INFLUENCE OF PERSONALITY AND ALCOHOL-USE ON RISKY DRIVING BEHAVIOUR AND ACCIDENT PRONENESS AMONG INJURED DRIVERS TREATED IN A TEACHING HOSPITAL IN OSHOGBO, NIGERIA (2015)
Road traffic accidents in Nigeria have been on the increase in recent years despite the various programme designed to reduce the carnage on Nigerian roads. Various factors have been implicated in accident aetiology and these include personal predilection to risky driving behaviour, accident proneness and alcohol use. Personality traits of extraversion and neuroticism have been implicated in accident proneness based on several studies carried out in developing countries. Therefore, this study examined the influence of personality types and alcohol use on risky driving behaviour and accident proneness among injured drivers treated in Ladoke Akintola University of Technology Teaching Hospital (LAUTECH), Osogbo, Osun State. A cross-sectional survey research design was used for the study. One hundred and twenty participants were selected from LAUTECH Orthopaedic, Accident and Emergency Physiotherapy Unit and outpatients’ clinic using consecutive recruitment. A questionnaire consisting of five (5) sections made up of standardized instruments was used in collecting data for the study. Informed consent and permission were obtained from both the participants and the hospital administrations before administering questionnaire on the respondents. Five (5) hypotheses were tested using t-tests and multiple regression analysis at P< 0.05 significant level. Results indicated that female participants were more prone to accident than their male counterparts {t (118) = 4.03; P<.01}. Also, those who had higher education scored higher on accident proneness than their counterparts with low education. {t (118) = -2.05, P<.05)}. Male drivers exhibited higher risky driving behaviours than female drivers {t(118) = 5.518; P <.01). Those who are lower in educational qualification are more risky in driving than those with higher education {t (118) = 2.617; P<.05}. Personality types (openness, conscientiousness, extraversion, agreeableness and neuroticism) and alcohol use predicted risky driving behaviour with joint contribution of 29.0% to the variance. Neuroticism (β = -0.29), openness to experience (β = 0.2) and alcohol use (β = 0.40) independently predicted risky driving behaviour. Personality types of extraversion (β = 0.-59) and agreeableness (β = 0.59) independently predicted accident proneness among the injured drivers. Alcohol and personality types influence accident proneness among injured drivers surveyed. This suggests that an abridged psychological assessment to identify the risk taking drivers before issuance of driver’s license and periodic re-evaluation with psycho-education be adopted